Semaphorins and neuropilins expression in salivary gland tumors. (22nd July 2015) - Fonseca, Felipe P.; Bingle, Lynne; Santos‐Silva, Alan R.; Lopes, Márcio A.; de Almeida, Oslei P.; de Andrade, Bruno A. B.; Mariano, Fernanda V.; Kowalski, Luiz P.; Rangel, Ana L. C. A.; Martins, Manoela D.; Meurer, Luise; Speight, Paul M.; et al.
Abstract : Background: Salivary gland tumors (SGT) account for 3–10% of all head and neck neoplasms, and little is known about their angiogenic properties. Despite semaphorins and neuropilins have been demonstrated to be prognostic determinants in many human cancers, they remain to be investigated in SGT. Therefore, the objective of this study was to analyze the clinical significance of the expression of class 3 semaphorins A (Sema3A) and B (Sema3B) and neuropilins‐1 (Np‐1) and neuropilins‐2 (Np‐2), in SGT. Methods: Two hundred and forty‐eight SGT were organized in tissue microarray paraffin blocks and expression of CD34, Sema3A, Sema3B, Np‐1, and Np‐2 was determined through immunohistochemistry. The immunoreactions were quantified using digital algorithms and the results correlated with clinicopathological parameters. Results: Malignant tumors had an increased vascular density than their benign counterparts and their increased vascular area significantly correlated with recurrences ( P < 0.05). Patients older than 40 years and the presence of recurrences determined an inferior survival rate ( P = 0.0057 and P = 0.0303, respectively). In normal salivary glands, Np‐1 and Np‐2 expression was restricted to ductal cells, whereas Sema3A and Sema3B were positive in the serous acinar compartment. Tumors were positive for all markers and the co‐expression of Np‐1/Np‐2 significantly correlated with the presence of paresthesia and advanced stages of the tumors ( P = 0.01 and P = 0.04, respectively). Conclusion: Sema3A, Sema3B, Np‐1, and Np‐2 may be involved in the pathogenesis of SGT, but their expression did not present a statistically significant prognostic potential in this study.